2013
DOI: 10.4103/0975-5950.117880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of AgNOR as a proliferative marker in oral leukoplakia: A morphometric analysis

Abstract: Background:Silver stainable nucleolar organizer regions (AgNORs) are replicatory markers which may have a place in objectively characterizing dysplasia.Materials and Methods:A study of various morphometric parameters related to AgNORs was performed in basal and parabasal layers of normal human oral epithelium, nondysplastic leukoplakia, and dysplastic leukoplakia employing photomicrographs of silver stained paraffin embedded sections using image analysis, to assess the usefulness of these parameters in disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Oral epithelial cells destined for “pre‐malignant” change are those most likely to already possess an inherently high proliferative activity. Using in vitro labelling studies to characterize oral epithelial activity, we have demonstrated a significant increase in proliferation indices for both increasingly severe dysplasia and worsening grades of OSCC differentiation; overall, increasing numbers of epithelial cells committed to cell division are characteristic of dysplastic PMD lesions . Of particular interest is the additional observation that “apparently normal‐looking” mucosa from OSCC patients may also exhibit abnormal proliferation profiles similar to that seen in dysplastic or neoplastic tissue …”
Section: Proliferationmentioning
confidence: 94%
See 1 more Smart Citation
“…Oral epithelial cells destined for “pre‐malignant” change are those most likely to already possess an inherently high proliferative activity. Using in vitro labelling studies to characterize oral epithelial activity, we have demonstrated a significant increase in proliferation indices for both increasingly severe dysplasia and worsening grades of OSCC differentiation; overall, increasing numbers of epithelial cells committed to cell division are characteristic of dysplastic PMD lesions . Of particular interest is the additional observation that “apparently normal‐looking” mucosa from OSCC patients may also exhibit abnormal proliferation profiles similar to that seen in dysplastic or neoplastic tissue …”
Section: Proliferationmentioning
confidence: 94%
“…Using in vitro labelling studies to characterize oral epithelial activity, we have demonstrated a significant increase in proliferation indices for both increasingly severe dysplasia and worsening grades of OSCC differentiation [8][9][10] ; overall, increasing numbers of epithelial cells committed to cell division are characteristic of dysplastic PMD lesions. 11,12 Of particular interest is the additional observation that "apparently normal-looking" mucosa from OSCC patients may also exhibit abnormal proliferation profiles similar to that seen in dysplastic or neoplastic tissue. 8 "Pre-malignant fields" probably precede tumour formation, with OSCC arising in a field subclone following specific, additional genetic damage; the field expands through oral epithelium at the expense of normal surrounding mucosa due to its inherently high proliferation rate.…”
Section: Proliferationmentioning
confidence: 99%
“…[ 43 ] The amount of AgNOR proteins can be exploited as a marker of cell proliferation and AgNOR quantification is a useful tool in the evaluation of the rate of cancer cell proliferation. [ 44 ] In the current study, the amount of AgNOR spots was substantially augmented in the nucleus of lung cancer mice induced by B(a)P, which specifies the hyperactivity of cell proliferative during cancer conditions. Our outcomes are in correlation with the previous report from another research group that during lung cancer, increased number of AgNOR may be related to high proliferative activity and aggressiveness of tumor cells.…”
Section: Discussionmentioning
confidence: 59%
“…Several reports have suggested that variations in AgNOR counts may reflect the state of activation or degree of malignancy of the lesion involved [ 16 ]. The AgNOR count is the most appropriate marker to differentiate between dysplastic and nondysplastic leukoplakia [ 17 ]. AgNOR analysis may be useful as a quantitative marker of incipient cellular alterations and hence would be helpful in assessing suspicious lesions and thus can be regarded as a valuable adjunct [ 18 ].…”
Section: Discussionmentioning
confidence: 99%